Anaerobic Digestion Processes Applications and Effluent Treatment (Green Energy and Technology,, 2018)
This book presents new application processes in the context of anaerobic digestion, such as phosphorus recovery, microbial fuel cell, and seaweed digestion. In addition, it introduces readers to a new technique for the modeling and optimization of anaerobic digestion (AD) processes. Chapters 1 and 2 review AD as a technique for converting a range of organic wastes into biogas, while Chapter 3 discusses the recovery of phosphorus from anaerobically digested liquor. Chapters 4 and 5 focus on new techniques for modeling and optimizing AD. In turn, Chapters 6 and 7 describe the state of the art in AD effluent treatment. The book's final three chapters focus on more recent developments, including microbial fuel cells (MFCs) (Chapter 8), seaweed production (Chapter 9), and enzyme technologies (Chapter 10).